Economic Benefits and Stakeholder’s Role In Community Forest Management In Rembang Regency, Central Java Province - Waridin Waridin; Aini Nur Furoida; Cici Musliha; Arisanti Ayu Wardhani (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2022)
This study aims to analyze the economic benefits of the Pesanggem Desa Sale community in Rembang Regency, Central Java, that is obtained from the use of corn farming, and to analyze the role of stakeholders in the implementation of CFM in Sale Village. Sources of data were obtained using the accidental sampling method to determine the number of respondents and the purposive sampling method for key informants, each of which amounted to 48 people and 14 people. The analytical method used is using the R/C ratio, co-management, and stakeholder analysis. The results showed that the R/C value for the cultivation of corn and cattle obtained a value of 1.96 & 1.70 respectively, meaning that it is feasible to run, and collaboration between stakeholders in implementing CFM is categorized as good, indicated by a value of 4, while stakeholders who have influence and interest high in quadrant II or key player, namely Forest Village Community Institution (FVCI), State-Owned Forestry Company (SOFC), Pesanggem and Agriculture Office (AO). This study indicates that CFM management has been running well where farming as a form of collaboration with the community has decent business prospects; evaluation of the implementation of co-management also showed promising results. In addition, the stakeholders involved have carried out their roles according to their respective roles and interests.